Pengaruh Strategi Kompetitif Terhadap Inovasi Perusahaan Yang Bergerak Di Industri Kertas - Winardi Suhardja (Universitas Tarumanagara, 2019)
This study aims to analyzing the influence of competitive strategies (cost leadership, differentiation and focusz) on corporate innovation (product, process and administrative innovations) in paper industry. The population in this study were employees of PT. X and PT. Y. The sampling method used was probability sampling and was determined to be 86 respondents of both firms. The analytical method used in this study is the analysis of the Stuctural Equation Model (SEM) with the AMOS program. The results showed that 1) Cost Leadership, Differentiation, Focus proved to have a significant positive effect on Product Innovation, 2) Cost Leadership, Differentiation, Focus proved to have a significant positive effect on Process Innovation, 3) Cost Leadership, Differentiation, Focus proved to have a significant positive effect on Administrative Innovation. For this reason, companies are expected to continue to innovate to increase customer satisfaction by paying attention to their competitive advantages such as maintaining cost advantages, maintaining strong brand identification and focusing on achieving competitive advantage.